Predictive grade of ultrasound synovitis for diagnosing rheumatoid arthritis in clinical practice and the possible difference between patients with and without seropositivity. Issue 2 (3rd March 2016) - Minowa, Kentaro; Ogasawara, Michihiro; Murayama, Go; Gorai, Misa; Yamada, Yusuke; Nemoto, Takuya; Matsuki, Yuko; Sugisaki, Nagachika; Ando, Seiichiro; Kon, Takayuki; Tada, Kurisu; Matsushita, Masakazu; et al.
Abstract : Objective. To determine the degree of contribution and the contributing factors of ultrasound in the diagnosis of rheumatoid arthritis (RA) in daily clinical practice and the predictive differences depending on seropositivity. Methods . We included 122 patients who presented with the main complaint of finger and/or wrist joint pain but for whom no definite diagnosis was reached or treatment strategy was provided. Ultrasound was performed on at least 22 joints (both wrist joints, proximal interphalangeal joint, and metacarpophalangeal joints), and patients were followed for ≥6 months. Factors contributing to RA diagnosis were determined and compared between seropositive and seronegative RA patients. Results. RA was diagnosed in 52 of 122 patients, in whom the American College of Rheumatology/European League Against Rheumatism (ACR/EULAR) classification criteria (odds ratio [OR] = 4.74, P = 0.01) and gray scale (GS) grade of 3 (OR = 3.64, P = 0.04) for ≥ 1 joint were the contributing factors. In seropositive RA, the ACR/EULAR criteria (OR = 15.53, P < 0.001) and power Doppler (PD) ≥ 2 for ≥ 1 joint (OR = 10.48, P = 0.0048) were the contributing factors. In seronegative RA, PD ≥ 1 for ≥ 1 joint contributed the most (OR = 20.00, P = 0.0044), but the ACR/EULAR criteria did not contribute to RA diagnosis ( P = 0.57). Conclusion. Ultrasound findings contributed to RA diagnosis in clinical practice. The contributing factors are different in the presence or absence of seropositivity, and ultrasound complementation was particularly useful in seronegative RA patients.